Implementation of the Ant Colony System Algorithm in the Lecture Scheduling Process - Tejo Herianto (Bahasa Indonesia, 2020)
Scheduling lectures using the ant algorithm is able to provide alternative solutions for scheduling lectures that want a certain time optimally. In this research, the method used is literature study. This literature study was carried out by reading books and literature related to scheduling and ant algorithms. In addition to using literature studies, researchers also use field studies. This is intended to get a true picture of the state of the institution by observing directly at the institution, by means of observation or data collection methods by conducting interviews on the parts involved in the process of preparing the class schedule. From the results of the analysis obtained: scheduling lectures using the ant algorithm is able to provide solutions in scheduling. The ant algorithm can be applied to create a class schedule with optimal results, the ant algorithm is able to provide solutions in the preparation of a lecture schedule that requires a certain time.